2020
DOI: 10.3390/su12166619
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Model of Consumers’ Perceptions, Attitudes and Behavioral Intention toward Organic Tea: Evidence from an Emerging Economy

Abstract: This study investigates factors that predict consumers’ perceptions of healthiness of organic tea. Furthermore, this study also examines the relationship between perceived healthiness and purchase intention with the mediating role of consumers’ attitudes toward organic tea. Because China has been the largest producer and the largest market of the global tea market, this study collects sample data from consumers at different tea stores in China. Using structural equation modelling to analyze data, results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…Bu et al (2020) conducted a study on the factors influencing the perception of healthiness of consuming organic tea in China. They identified that tea quality, services to customers and selling store's attributes could significantly predict consumers' perception of organic tea.…”
Section: Literature Review Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu et al (2020) conducted a study on the factors influencing the perception of healthiness of consuming organic tea in China. They identified that tea quality, services to customers and selling store's attributes could significantly predict consumers' perception of organic tea.…”
Section: Literature Review Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…They further argued that perceptions of the healthiness of organic tea could explain its buying behaviour. In their research limitations segment, Bu et al (2020) urged similar studies to be conducted in South Asian countries that might help generalize organic products' buying behaviour. They further suggested including different variables like emotions and behaviour norms.…”
Section: Literature Review Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Research on organic food consumption focused mainly on developed countries [11], however, countries with developing or emerging economies maintain a nascent market for organic food [12,13]. Most organic food is produced in developing countries, however, approximately 90% of its consumption occurs in developed countries [14].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, researchers highlighted the need to fulfill this gap by exploring motives or factors that promulgate consumer's actual consumption [23,24,26]. In this regard, some researchers argued that testing additional constructs and articulating existing sophisticated theoretical frameworks can provide significant insights to understanding the actual consumption of organic food consumers [12,24,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous research by Beneke et al (2013) found that product quality and related price have a positive and significant affect on consumers' desire to purchase the product, this because the product purchased has the value which consumers want. Then, prior research by Bu et al (2020) found that product quality has a positive and significant affect on brand attitudes. Mostafa & Elseidi (2018) found that price consciousness has a positive and significant affect on brand attitudes.…”
Section: Introductionmentioning
confidence: 98%